LITERATUR REVIEW: GAMBARAN PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI PESANTREN - Aini, Ririn Nur; Nuryati, Tati (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Islamic boarding schools as religious educational institutions have an important role in improving human resources. Islamic boarding schools with various activities and lack of knowledge regarding the implementation of Clean and Healthy Behavior (PHBS) can pose a risk of disease transmission and worsen environmental conditions around the Islamic boarding school. Objective: To describe the description of PHBS in Islamic boarding schools. Method: The method used in this study is the literature review method. Result: The results show that a good description of the implementation of PHBS is closely related to knowledge and high information related to health. Islamic boarding schools that provide attention and knowledge related to PHBS show a good picture of the attitude and implementation of PHBS students. Islamic boarding schools that have carried out promotive, preventive, curative and rehabilitative interventions show the high implementation of PHBS for students. The improper implementation of PHBS by students is usually related to consumption of risky foods, not keeping the environment clean and not maintaining personal hygiene.